2010
DOI: 10.1007/s00276-010-0706-5
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular nerve entrapment in the infratemporal fossa

Abstract: The posterior trunk of the mandibular nerve (V(3)) comprises of three main branches. Various anatomic structures may entrap and potentially compress the mandibular nerve branches. A usual position of mandibular nerve (MN) compression is the infratemporal fossa (ITF) which is one of the most difficult regions of the skull base to access surgically. The anatomical positions of compression are: the incomplete or complete ossified pterygospinous (LPs) or pterygoalar (LPa) ligament, the large lamina of the lateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…Pterygospinous bar ridge separates the trunk of lingual into anterior and posterior branches. Anterior fibres may get compressed because of their course between the tensor veli palatini muscle and the bony ridge [31] or because of a large lateral pterygoid plate [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Pterygospinous bar ridge separates the trunk of lingual into anterior and posterior branches. Anterior fibres may get compressed because of their course between the tensor veli palatini muscle and the bony ridge [31] or because of a large lateral pterygoid plate [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…It normally pierces the posterior half of the buccinators muscle to arborize extensively on the buccal surface of the cheek (Tubbs et al, ). However, some authors reported that the buccal nerve was a mixed nerve, which provide the branches to the lateral pterygoid muscle and temporal muscle (Kim et al, ; Piagkou et al, ; Davies et al, ).…”
Section: Anatomymentioning
confidence: 99%
“…It is generally described that the nerve to the lateral pterygoid nerve originates mainly from the buccal nerve (Fig. A) (Gray and Williams, ; Kim et al, ; Piagkou et al, ). It is the most inconsistent of all the individual branches of the entire trigeminal nerve (Shankland, ).…”
Section: Anatomymentioning
confidence: 99%
“…Compression of motor branches of mandibular nerve can lead to paresis or weakness of the innervated muscles. 11 Elongation of the lateral lamina of the pterygoid process could result in weakening of the medial pterygoid muscle and paresthesia of the inner aspect of the cheek. Probable compression of the lingual nerve could lead to the weakening of general sensation from anterior two-thirds of the tongue unilaterally or may cause neuralgia.…”
Section: Discussionmentioning
confidence: 99%
“…Anterior fibers may get compressed because of their course between the tensor veli palatini muscle and the bony ridge 20 or because of a large lateral pterygoid plate. 11,21,22…”
Section: Discussionmentioning
confidence: 99%